2017
DOI: 10.1126/science.aam8378
|View full text |Cite
|
Sign up to set email alerts
|

An unusual white dwarf star may be a surviving remnant of a subluminous Type Ia supernova

Abstract: Subluminous Type Ia supernovae, such as the Type Iax-class prototype SN 2002cx, are described by a variety of models such as the failed detonation and partial deflagration of an accreting carbon-oxygen white dwarf star or the explosion of an accreting, hybrid carbon-oxygen-neon core. These models predict that bound remnants survive such events with, according to some simulations, a high kick velocity. We report the discovery of a high proper motion, low-mass white dwarf (LP 40-365) that travels at a velocity g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
116
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 46 publications
15
116
2
Order By: Relevance
“…After their initial phase of radius expansion, the remnants from model 2 cool and contract as low-mass WDs incapable of any further nuclear burning. model 2 can evolve near the locations on the HR diagram for GD 492 (LP 40-365) and J1603-6613 (Vennes et al 2017;Raddi et al 2018aRaddi et al ,b, 2019, and remain there for the 10 6 -10 7 years expected from their kinematics and location in the galaxy. The ejection velocities for our models are somewhat higher than the ≈600 km/s inferred by Raddi et al (2018aRaddi et al ( , 2019 for these objects when accounting for the rotation velocity of the galactic disk.…”
Section: Post-interaction Evolution With Mesamentioning
confidence: 92%
“…After their initial phase of radius expansion, the remnants from model 2 cool and contract as low-mass WDs incapable of any further nuclear burning. model 2 can evolve near the locations on the HR diagram for GD 492 (LP 40-365) and J1603-6613 (Vennes et al 2017;Raddi et al 2018aRaddi et al ,b, 2019, and remain there for the 10 6 -10 7 years expected from their kinematics and location in the galaxy. The ejection velocities for our models are somewhat higher than the ≈600 km/s inferred by Raddi et al (2018aRaddi et al ( , 2019 for these objects when accounting for the rotation velocity of the galactic disk.…”
Section: Post-interaction Evolution With Mesamentioning
confidence: 92%
“…It is possible this explosion does not completely disrupt the white dwarf, leaving a bound remnant 149 . Surviving examples of such incomplete explosions may have been discovered in our Galaxy as fast-moving white dwarfs with unusual abundances 150,151 .…”
Section: The Thermonuclear Supernova Zoomentioning
confidence: 99%
“…Recently,Kepler et al (2016a) identified a WD having an O-dominated atmosphere with traces of Ne and Mg, that could be the bare core of a Super-AGB star. Finally, another O-and Ne-rich WD but with a very low mass was discovered byVennes et al (2017).…”
mentioning
confidence: 95%